2011
DOI: 10.1213/ane.0b013e31820ad4d9
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Opioids and Sedatives and Time Until Death After Withdrawing Mechanical Ventilation and Vasoactive Drugs in a Dutch Intensive Care Unit

Abstract: Dutch patients who die in the ICU, or die after discharge from the ICU, die after MV and/or VAs are withdrawn. When treatments are withdrawn, death follows within 1 hour in most patients, which is a reflection of the severity of illnesses. At least 80% of patients receive opioids, and 67% receive sedatives until death. Fentanyl is the most used opioid, whereas midazolam is the most used sedative. Dosages of opioids and sedatives did not significantly exceed the ranges described as usual in the international li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…A noticeable difference compared with the USA, where such decisions are made by the responsible physician in collaboration with family members or a surrogate decision maker of the patient [19,22]. When treatment is believed to be futile by the multidisciplinary team, in most cases treatment is withdrawn rather than withheld [23]. Among patients in whom treatment was withdrawn, a large percentage of patients with severe CNS failure were presented.…”
Section: Discussionmentioning
confidence: 99%
“…A noticeable difference compared with the USA, where such decisions are made by the responsible physician in collaboration with family members or a surrogate decision maker of the patient [19,22]. When treatment is believed to be futile by the multidisciplinary team, in most cases treatment is withdrawn rather than withheld [23]. Among patients in whom treatment was withdrawn, a large percentage of patients with severe CNS failure were presented.…”
Section: Discussionmentioning
confidence: 99%
“…This statement is not in concordance with our own experience. The withdrawal rate in our Dutch ICU is 83% of the patients who died in the ICU [3]. This result is fully supported by the ETHICUS (Ethics in European Intensive Care Units) study, which reported that withdrawal of treatment is a generally accepted form of end-of-life care in Europe, especially in Northern Europe [4].…”
mentioning
confidence: 64%
“…2,5,39 In a study of 60 adult patients in a Dutch intensive care unit, 80% received opioids and 67% received sedatives during withdrawal of life support. 40 Those who did not receive drugs were more likely to have acutely devastating neurologic disease. 40 …”
Section: Discussionmentioning
confidence: 99%
“…40 Those who did not receive drugs were more likely to have acutely devastating neurologic disease. 40 …”
Section: Discussionmentioning
confidence: 99%